Cultural Studies in German as a Foreign Language in Thailand: : Learning and Teaching about the Cultures of German Speaking Countries in the Context of Thai Higher Education - Kaewwipat, Thanakon (Journal of Letters, 2020)
Teaching cultural studies in the field of German as a Foreign Language in Thailand tends to focus on providing information and facts about the geography, political-administrative systems and cultural issues of the Federal Republic of Germany. This approach doesn’t conform with current trends in learning and teaching cultural studies in the wider academic community of German as a Foreign Language, which place more emphasis on the culture of German speaking countries. This article discusses a theoretical framework in relation to learning and teaching about the cultures of German speaking countries, and investigates the possibilities and limitations of the tangible application of this concept in the context of higher education in Thailand.